2021
DOI: 10.3390/healthcare9080947
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Nursing Simulation Using Mixed Reality: A Scoping Review

Abstract: Mixed reality (MR) has recently been suggested as a new educational tool for nursing simulation. However, few studies have assessed the use and evaluation of MR nursing simulations. Therefore, this review identified studies of MR nursing simulations through a scoping review using the framework proposed by Arksey and O’Malley. The studies reviewed were found through DBpia, RISS, PubMed, CINAHL, and Google Scholar. Each study was analyzed, and data were abstracted into publication characteristics, simulation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Mixed reality (MR) is currently used in various educational and clinical settings ( Kim, Choi, & Kim, 2021 ), and its importance is increasing given changes in the educational environment due to the COVID-19 pandemic. Unlike virtual reality (VR), which creates a simulated environment that is not real, MR synthesizes virtual objectives or information with the real world, allowing users to experience a blended reality through devices such as HoloLens ( Kaplan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed reality (MR) is currently used in various educational and clinical settings ( Kim, Choi, & Kim, 2021 ), and its importance is increasing given changes in the educational environment due to the COVID-19 pandemic. Unlike virtual reality (VR), which creates a simulated environment that is not real, MR synthesizes virtual objectives or information with the real world, allowing users to experience a blended reality through devices such as HoloLens ( Kaplan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This sort of interaction can provide a sense of personal touch and immersion in situations that cannot be experienced face-to-face in the real world ( Yoo, Kim, Koo, & Song, 2018 ), and it can generate interest as users learn while operating the program themselves ( Hauze & Marshall, 2020 ). MR is suitable for learning content that is difficult to observe directly or to explain in text and can be applied in risky experiments ( Kaplan et al, 2021 ; Kim et al, 2021 ; Yoo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scoping reviews are suited to identifying knowledge and research gaps prior to, for example, conducting a systematic review [ 28 ]. Scoping reviews increasingly assess the quality and methodological rigour of included studies e.g., [ 29 , 30 ] therefore, we used the Hawker Tool [ 31 ] because it is suitable for assessing the quality and rigour of studies with various designs and to indicate the level of confidence with which findings should be assessed.…”
Section: Methodsmentioning
confidence: 99%
“…A scoping review of MR simulation in nursing education (Kim, Choi, and Kim 2021) found the HoloLens introduced by Microsoft in 2016 was the most commonly used device and had a number of advantages for nursing education which requires students to develop both clinical skills and professional judgement. The MR was also able to avoid some of the negative aspects of VR such as lack of spatial awareness that can lead to nausea, or headaches or blurred vision while fully immersed in VR.…”
Section: Benefits Of Mr In Trainingmentioning
confidence: 99%
“…To explore the potential of Mixed Reality (MR) providing a stronger connectivity between theoretical and applied content, to 'prioritise applying theory in context specific and workable ways' (Greenway, Butt, and Walthall 2019, p. 4), research was undertaken at Toi Ohomai Institute of Technology / Te Pūkenga (Toi Ohomai / Te Pūkenga) using science-based content in nursing degrees. This leads on from the findings on measuring student progress in 2019 by Nichols, cited in Collins and Ditzel (2021, p. 181), and student success in Australia undertaken by the University of Canberra (Frost, Delaney, and Fitzgerald 2020), and desk-based research on the use of MR in nursing education by Kim, Choi and Kim (2021). The research was to serve as a reference point for the student experience and be available for comparisons with similar HoloLens implementations in three other Aotearoa New Zealand ITP nursing institutions.…”
Section: Introductionmentioning
confidence: 99%